Fruitlicious enterprise chillin’ ice cream - Mohd Fauzi, Nur Arina Sofia; Mohd Isnudin, Nur Athirah; Rosli, Nurul Batrisya; Maskuri, Nurul Hanis; Wan Khairul Anuar, Wan Ummi Qistina (2021)
This business is based on partnership typed of company where it consists of 5 members which hold important positions in the company such as Chief Executive Officer or CEO, Administrative Manager, Marketing Manager, Operational Manager and Financial Manager. For the business capital, it is amounted in about RM250,000 where the total contribution is made from each partner on RM50,000. Coconut Ice Cream with Gula Melaka is the signature menu at our store other than several fruity bar soft ice cream with tagline ‘Yum yum, so fruitylicious’ is located at Bandar Hilir, the central city of Melaka with address of No.39, Jalan KSB 11, Taman Kota Syahbandar, 75200 Malacca, Malaysia. Fruitylicious Enterprise is a company that focuses on cooling food production in Malaysia and ice cream is one of the highest demand food or dessert by Malaysian and people all over the world. It is really suitable to serve during sunny days especially during hot weather. The soft, fresh and cool texture with a very attractive packaging gives an opportunity Moreover, the simple steps and ingredients used give a lot of benefits to our company and we are highly confident that our market can be easily developed and spread all over the country. To make it more interesting, we decided to make some innovation by implying our creativity and modern element in the delivery process of this ice cream. This is shown by there are the implementation of posting and delivery without have to freeze the ice cream and just send it in a liquid state condition but still manage to preserve the freshness of the soft fruity ice cream. It is to ensure that people who are busy also can taste the uniqueness of our ice cream without having to bring the cool box or any thermos just to preserve the condition of ice cream from melting. With all the capitals accumulated, we are hoping and wishing to make Chillin’ Ice Cream Café able to achieve outstanding demand from the consumer and our business is expected to commence on 2021 with the vision to be the main supplier of innovative soft ice cream worldwide. This will be achieved with the full cooperation and efforts among the partners to promote company for better condition. We also will expect that our business will become more developed in the near future with the new innovation element in our ice cream as it is extraordinarily attractive. It is also in our hope that the demand will increase not only during any occasion but might be a new daily must eat dessert. This will give more advantages for us to make our product more profitable and stable in the long run, thus sustain for generations.